Implementasi Pemanfaatan Barang Bekas Dalam Menanamkan Karakter Peduli Lingkungan Anak Usia 5-6 Tahun - Ananda, Althaf Riza; Tanfidiyah, Nur (UIN Raden Mas Said Surakarta, 2023)
This research aims to determine the growth of the environmentally caring character of children aged 5-6 years through the use of used goods. The method in this research is using qualitative research. The data collection techniques used were passive participant observation, structured interviews, and documentation. Based on the results of this research, it can be concluded that the implementation of the use of used goods in instilling the character of caring for the environment in children aged 5-6 years at RA Nurhasanah Cileungsi Bogor for the 2021/2022 academic year, (1) learning planning has been carried out by preparing RPPH which refers to themes, indicators , and the goals of learning. (2) implementation of used goods utilization activities starts from introducing types of used goods, introducing care for the environment and making works from used goods. Then in the closing activity, recalling is carried out with the children to train the children's memory and review the material given by the teacher. (3) the assessment is carried out by the teacher using checklist assessment techniques.